PENGARUH LATIHAN ELASTIC BAND TERHADAP POWERR OTOT TUNGKAI DALAM SHOOTING CABANG OLAHRAGA SEPAK BOLA - Kamaluddin, Najib; Risma, Risma; Ropi, Ucu Abdul (Faculty of Teacher Training and Education, 2024)
The study wanted to find out the effect of elastic band training on leg muscle power in shooting soccer. The population used in this study was SSB Satria FC with a sample of 22 people using the total sampling technique. The instrument used is the standing broad jump test. By analyzing the data using the t-test on the research hypothesis. Based on the results of the study it was found that Sig 2-Tailed had a value of 0.000, so this study had different standing broad jump test results after the treatment group and the control group. So, the results of the elastic band training itself have an influence on the results of increasing leg power.